In situ structural changes of amorphous diopside (CaMgSi2O6) up to 20 GPa: A Raman and O K-edge X-ray Raman spectroscopic study. (1st April 2016) - Moulton, Benjamin J.A.; Henderson, Grant S.; Fukui, Hiroshi; Hiraoka, Nozomu; de Ligny, Dominique; Sonneville, Camille; Kanzaki, Masami
Abstract: Diopside, CaMgSi2 O6, is an important analogue for depolymerized silicate melts. We have used the complimentary spectroscopies, X-ray Raman Scattering (XRS), X-ray absorption near edge structure (XANES) and Raman, to investigate diopside glass in situ to 20 GPa. We observe a stark change in behavior of CaMgSi2 O6 near 4 GPa that corresponds to a major change in the rate of inter-tetrahedral angle (∠Si–O–Si) closure. Below 4 GPa, the ∠Si–O–Si closes rapidly at 2–3°/GPa whereas above 4 GPa it decreases by ∼1°/GPa. A distinct shift to higher wavenumbers of the 870 and 905 cm −1 Raman bands are observed at 1.3 GPa suggesting that Q 0 species have been completely converted to Q 1 or higher Q n species. XRS measurements at the O K -edge suggest that [5] Si is formed by 3 GPa. This formation is accompanied by a rapid decrease in the ∠Si–O–Si and a decrease in Q 0 species. A linear increase in the geometric mean of the high frequency envelope, the χ b value, from 999 to 1018 cm −1 suggests that the conversion of NBO to BO is continuous up to 14 GPa. Above 14 GPa, the Raman spectra show an obvious negative shift in both, the high frequency peak maximum, and the χ b position. Simultaneously, the low frequency envelope looses its asymmetry at 14 GPa. This may be explained by either a loss of a vibrational mode in the range 1000–1200 cm −1 and/or the formation of [6] Si. The structural evolution of CaMgSi2 O6 correlates well with a major change in the compressibility and diffusivity around 5 GPa.